Analisis Permintaan Minyak Kelapa (Coconut Crude Oil) Indonesia di Pasar Internasional - Sukmaya, Syahrul Ganda (AGRARIS: Journal of Agribusiness and Rural Development Research, 2017)
The world demand of coconut oil or Coconut Crude Oil (CCO) was 2.18 million tons per year in 2014. The market share of Indonesian palm oil in international market was the second largest after the Philippines. Vegetable oil market fluctuations in international markets was influenced by economic conditions of CCO consumer countries therefore influenced on oil exports. The purpose of this study was to analyze demand elasticity of Indonesian palm oil in international market and it competition with other producers. This study used secondary data, i.e annual data of Indonesian coconut crude oil exports and other exporting countries in international market from 1984 to 2015. The market demand analysis approach using AIDS (Almost Ideal Demand System) and competition with the analysis of comparative advantage of Revealed Comparative Advantage (RCA) was used. Results showed that Indonesian coconut oil commodities has a comparative advantage in international market. Moreover, increasing demand for imports of coconut crude oil in international market would be beneficial for Indonesia since it may increase Indonesian market share.